2021
DOI: 10.3390/ijms22042151
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Fragments as Biomarkers of Islet β-Cell Death in Obesity and Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) typically occurs in the setting of obesity and insulin resistance, where hyperglycemia is associated with decreased pancreatic β-cell mass and function. Loss of β-cell mass has variably been attributed to β-cell dedifferentiation and/or death. In recent years, it has been proposed that circulating epigenetically modified DNA fragments arising from β cells might be able to report on the potential occurrence of β-cell death in diabetes. Here, we review published literature of DNA-based β-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
15
1
Order By: Relevance
“…[45] In this respect, liquid biopsies, such as cfDNA and circulating histones/nucleosomes ("epimarks"), have been proposed as promising biomarkers for adult NAFLD. [10][11][12][13][14][15][16][17][18][31][32][33] Although previous evidence in adults with NAFLD demonstrated that circulating levels of total cfDNA are different in comparing patients with different stages of disease, [48] we found that total cfDNA concentration in children was unchanged among the different groups of comparison (controls, NASH, and no NASH). Even if this finding suggests that the levels of absolute cfDNA could not be a good parameter for monitoring disease progression, further studies on a larger number of patients are required to support this assumption.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…[45] In this respect, liquid biopsies, such as cfDNA and circulating histones/nucleosomes ("epimarks"), have been proposed as promising biomarkers for adult NAFLD. [10][11][12][13][14][15][16][17][18][31][32][33] Although previous evidence in adults with NAFLD demonstrated that circulating levels of total cfDNA are different in comparing patients with different stages of disease, [48] we found that total cfDNA concentration in children was unchanged among the different groups of comparison (controls, NASH, and no NASH). Even if this finding suggests that the levels of absolute cfDNA could not be a good parameter for monitoring disease progression, further studies on a larger number of patients are required to support this assumption.…”
Section: Discussioncontrasting
confidence: 64%
“…cfDNA methylation and circulating histones have now been shown to be useful biomarkers for diagnosis, prognosis, and/or response to therapy in different type of cancers, and recently also in some chronic diseases, such as obesity and type 2 diabetes. [ 11,42,43 ] These findings are of particular relevance for diseases in which biomarkers may help in understanding their natural history, such as for NAFLD/MAFLD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports showed that GCK methylation is a more suitable marker than INS methylation for the detection of β-cell death in T1DM and therefore can present an early diabetes biomarker [9]. Furthermore, the recent study of Arosemena et al reported that none of the four groups (lean controls with normal glucose tolerance; overweight/obese with normal glucose tolerance; impaired glucose tolerance; and T2DM patients) showed statistically significant differences in INS methylation compared to the healthy controls [43]. These findings are in agreement with our observations in T2DM, where INS methylation showed a low capacity to discriminate T2DM, and GCK methylation revealed the best capacity, highlighting its potential clinical value as a minimally invasive biomarker for T2DM personalized management.…”
Section: Discussionmentioning
confidence: 98%
“…In future studies, the alignment of DNA methylation, fragmentome, and topological analysis of cell-free DNA in a targeted or genome-wide manner is expected to have a beneficial impact on clinical practice [ 15 ]. In diseases with metabolic disorders, such as type 2 diabetes [ 16 , 17 ] and coronary artery disease [ 18 ], there are also corresponding cells, such as pancreatic β-cell, whose cell-free DNA fragments are modified, making these cells potential biomarkers of the diseases.…”
Section: Discussionmentioning
confidence: 99%